Mixed Layer Temperature Budget in the Arabian Sea During Winter 2019 and Spring 2019: The Role of Diapycnal Heat Flux. Issue 2 (10th February 2023) - Jofia, J.; Girishkumar, M. S.; Ashin, K.; Sureshkumar, N.; Shivaprasad, S.; Pattabhi Ram Rao, E.
Abstract: Sea surface temperatures (SSTs) simulated by almost all models in Coupled Model Inter‐comparison Project phase five are consistently colder (∼−1°C to −4°C) than the observation in the northern Arabian Sea (AS) during winter and spring. These biases significantly weaken the seasonal and extended summer monsoon prediction skills and climate change projection's reliability in this region. To understand the relative contribution of diapycnal heat flux ( J h ) compared to other terms in the mixed layer (ML) temperature (MLT) budget during these two seasons, we use time series of vertical profiles of microstructure shear measurements collected in the northeastern AS (NEAS) at 18.4°N and 67.4°E during January 10–17, 2019 (W19) and May 7–21, 2019 (S19). It is found that the vertical processes term and net surface heat flux together determine the bulk of MLT tendency during S19 and W19, and the contribution of the horizontal advection and J h is relatively smaller. The mean value of J h (∼−2 W m −2 ) at the base of the ML shows a comparable magnitude during W19 and S19, and the median values of diapycnal diffusivity ( K ρ ) at the ML base are not significantly different between W19 (∼3.1 × 10 −6 m 2 s −1 ) and S19 (∼5.2 × 10 −6 m 2 s −1 ). Besides, K ρ and J h values were estimated using different K ρ ‐Richardson number ( Ri ) based interior ocean parameterization schemes at the ML base in the NEAS overestimated with respect to observation. The alleged role of overestimation of K ρ and J h in parameterization schemes on model simulation of cold SST bias in the AS is also discussed. Plain Language Summary: Sea surface temperature (SST) in the Arabian Sea (AS) plays a significant role in regulating the Indian summer monsoon. However, the SST simulated by almost all models in Coupled Model Inter‐comparison Project phase five is consistently colder (∼−1°C to −4°C) than observations in the northern AS during winter and spring. In this study, the alleged role of inappropriate representation of diapycnal heat flux at the mixed‐layer base through parameterization scheme in ocean model is investigated using the microstructure data collected during two scientific cruises in the northeastern AS during winter and spring 2019. It is found that the contribution of diapycnal heat flux is negligibly small compared to atmospheric fluxes and vertical processes on the modulation of SST in the northeastern AS during winter and spring. Besides, the present study demonstrated that diapycnal heat flux estimated using different Richardson number‐based interior ocean parameterization schemes at the mixed‐layer base in the northeastern AS shows higher values than observation. These characteristics suggest that parameterized diapycnal heat flux at the mixed‐layer base may also act as a critical process to generate anomalous cold SST bias in the ocean model. Key Points: The importance of diapycnal heat flux compared to other terms in the mixed layer temperature budget in the Arabian Sea is examined The contribution of the diapycnal heat flux at the base of the mixed layer is relatively smaller and comparable during winter and spring The diapycnal heat flux estimated by Richardson number‐based interior ocean parameterization schemes shows higher values than observation